Arena Komunikasi Politik di Indonesia: Bagaimana Masyarakat Sipil Menggunakan Media Baru sebagai Komunikasi Politik - Wisnu Martha Adiputra; Budi Irawanto; Novi Kurnia (Program Studi Ilmu Komunikasi, 2023)
This research seeks to explain the arena of political communication in Indonesia for civil society groups to use new media from 2010 to 2020. The context of this time shows the increasingly complex development of democracy and new media, including the presence of social media. The research was conducted using the case study method by exploring three cases of civil society groups, namely Remotivi, Combine Resource Institution, and Zero Kilometer Makassar. This study departs from the hypothesis that the use of new media by civil society groups can encourage a more democratic process of political communication. This study found that the presence of new media has not been able to encourage civil society to use the arena of political communication properly. Judging from the aspect of the arena, which consists of existence, regulation, relations, and public space, it turns out that it has not been able to encourage a democratic political communication process even though new media has been used in communication actions by civil society groups.This research seeks to explain the arena of political communication in Indonesia for civil society groups to use new media from 2010 to 2020. The context of this time shows the increasingly complex development of democracy and new media, including the presence of social media. The research was conducted using the case study method by exploring three cases of civil society groups, namely Remotivi, Combine Resource Institution, and Zero Kilometer Makassar. This study departs from the hypothesis that the use of new media by civil society groups can encourage a more democratic process of political communication. This study found that the presence of new media has not been able to encourage civil society to use the arena of political communication properly. Judging from the aspect of the arena, which consists of existence, regulation, relations, and public space, it turns out that it has not been able to encourage a democratic political communication process even though new media has been used in communication actions by civil society groups.